The Doctrine of Natural Law as the Ideology of the Western Legal Tradition - E. Komleva (Теоретическая и прикладная юриспруденция)
The article examines classical natural law as the ideological foundation of the legal tradition in the Western world. As the author demonstrates, natural law was inherently linked to the legal traditions of antiquity and the Middle Ages, shaping both the dominant historical type of legal thinking and the models of legal regulation implemented within the respective traditions for the behavior of participants in legal communication. The preeminent position of natural law was determined by historical context as well as the specificities of the legal orders corresponding to that historical type. According to the author, the doctrine of classical natural law has become the ideological bedrock of the Western legal tradition in all its diverse aspects and manifestations. It can, therefore, be asserted that the Western legal tradition, viewed from this perspective, constitutes a collection of legal ideas characteristic of Western civilization and intended for the modernization of non-Western states.